Research Data Management - A European Perspective. - Filip Kruse; Jesper Boserup Thestrup (Current topics in library and information practice., 2017)
This new series presents and discusses new and innovative approaches used by professionals in library and information practice worldwide. The authors are chosen to provide critical analysis of issues and to present solutions to selected challenges in libraries and related fields, including information management and industry, and education of information professionals. The book series strives to present practical solutions that can be applied in institutions worldwide. It thereby contributes significantly to improvements in the field.